IMR 665: Management of Audio Visual Records & Archives. Individual assignment: Article summary / Mohamad Hashime Othman - Othman, Mohamad Hashime (2015)
Article on: Article 1 - “Clear skies or cloudy forecast? Legal challenges in the management and acquisition of audiovisual materials in the cloud” Article 2 - “Archives and records management in Kenya: problems and prospects”